2020
DOI: 10.1002/slct.202000137
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2‐Cyanoquinazolin‐4‐ones from 3′,5′‐Dichloro‐1H‐spiro(quinazoline‐2,4′‐[1,2,6]thiadiazin)‐4(3H)‐ones

Abstract: A two‐step synthesis of five 2‐cyanoquinazolin‐4‐ones starting from 3,4,4,5‐tetrachloro‐4H‐1,2,6‐thiadiazine is presented. The latter reacts with 2‐aminobenzamides to give 3′,5′‐dichloro‐1H‐spiro(quinazoline‐2,4′‐[1,2,6]thiadiazin)‐4(3H)‐ones, which can be degraded with either excess polymer bound triphenylphosphine or catalytic amounts of benzyltriethylammonium iodide to give the 2‐cyanoquinazolin‐4‐ones in 46–97% yields. The single crystal X‐ray diffraction analysis of 2‐cyanoquinazolin‐4(3H)‐one is also rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Interestingly, earlier efforts to prepare N-Me diazepine 18 from tetrachlorothiadiazine 3 and 2-amino-N-methylbenzamide gave only 3′,5′-dichloro-3-methyl-1H-spiro[quinazoline-2,4′- [1,2,6]thiadiazin]-4(3H)-one. 23 The potential for selective ring degradations of the parent diazepine 4a was then investigated. DSC studies of recrystallized diazepine 4a showed a mp at 218.7 °C (onset), followed by a decomposition at 251.7 °C (onset), to give polar intractable material (baseline by TLC).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Interestingly, earlier efforts to prepare N-Me diazepine 18 from tetrachlorothiadiazine 3 and 2-amino-N-methylbenzamide gave only 3′,5′-dichloro-3-methyl-1H-spiro[quinazoline-2,4′- [1,2,6]thiadiazin]-4(3H)-one. 23 The potential for selective ring degradations of the parent diazepine 4a was then investigated. DSC studies of recrystallized diazepine 4a showed a mp at 218.7 °C (onset), followed by a decomposition at 251.7 °C (onset), to give polar intractable material (baseline by TLC).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Our interest in quinazolines began with 3′,5′-dichloro-1H-spiro(quinazol [1,2,6]thiadiazin)-4(3H)-ones 1 that can be synthesized in 3 steps startin tetrachlorothiadiazine 2 [3] (Scheme 1). Interestingly, spirocycle 1a (R = H) can decomposed to 4-oxo-3,4-dihydroquinazoline-2-carbonitrile (3) [4] (Scheme 1 recently, while investigating the stability of 4-chlorobenzo[e] [1,2,6]thiadiaz b] [1,4]diazepin-10(11H)-one (4), we found that upon heating in MeOH/AcOH (9 was converted in 92% yield to the isomeric 2-(4-chloro-1,2,5-thiadiazol-3-yl)quin 4(3H)-one (5) [5] (Scheme 1). We attributed this transformation to an acid-ca nucleophilic addition to the thiadiazine 4 followed subsequent Wagner-Meerwe leading to the observed ring contractions [5].…”
Section: Resultsmentioning
confidence: 99%